Pressure effect on electronic structure and magnetic properties of MB₆ and MB₁₂ borides - Grechnev, G.E.; Baranovskiy, A.E.; Logosha, A.V.; Panfilov, A.S.; Fil, V.D.; Ignatova, T.V.; Shitsevalova, N.Yu.; Eriksson, O. (Физика и техника высоких давлений, 2006)
Theoretical and experimental studies of the pressure effect on electronic structure and magnetic properties of MB₆ and MB₁₂ borides are carried out to determine the electronic ground states and interactions responsible for the bulk and magnetic properties of these compounds. The band structure and total energy E were calculated ab initio for a number of atomic volumes, providing the equation of states, E(V), bulk moduli B, magnetic moments and susceptibilities. The temperature and pressure dependencies of magnetic susceptibility were also experimentally studied for a number of borides using a pendulum-type magnetometer. In semimetallic EuB₆ the paramagnetic Curie temperature is found to be increasing with pressure, dθ/dP = 0.44 ± 0.03 K/kbar, whereas in closely related GdB₆ compound the pressure effect is lower in magnitude but opposite in sign: dθ/dP = –0.17 ± 0.03 K/kbar. The peculiar details in electronic structures are found to be responsible for distinctions in magnetic ordering and the pressure effects on indirect f−f interactions.